Impact of Social Media Platform on Entrepreneurial Venture: A Technopreneurship Perspective - Udoudom, Uduak; Brown, George; George, Kufre (Journal of Business Management and Economic Development, 2024)
This conceptual research explores the impact of social media platforms on entrepreneurial ventures, specifically from a technopreneurship perspective. The study examines the ways in which social media platforms have become integral tools for technopreneurs, who leverage technology and innovation in their entrepreneurial pursuits. The study highlights key findings related to the influence of social media on business strategy, marketing, customer engagement, and overall venture success within the technopreneurial landscape. Additionally, the research examines challenges and opportunities arising from the relationship between social media and technopreneurship, shedding light on evolving trends and best practices. The findings will contribute valuable insights for entrepreneurs, researchers, and policymakers seeking to understand and harness the transformative power of social media in the dynamic realm of technopreneurship.